1998
DOI: 10.1029/98gl01584
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic observation of HCl degassing from Soufriere Hills Volcano, Montserrat

Abstract: Abstract.Open-path Fourier transform infrared (FTIR) spectroscopic techniques were employed to study gas emissions from Soufriere Hills volcano in July-August 1996. Observations were made using both volcanic and artificial sources of infrared energy. Column amounts of HC1 fall in the range 1-100 ppmv m but other species expected in the gas phase, notably SO2, are not apparent in the spectra. The minimum detection limit for SO2 in these data indicates that the HC1/SO2 molecular ratio exceeded 10. Scaled against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 14 publications
1
16
1
Order By: Relevance
“…5). This amount is significantly lower than that observed by open-path infrared measurements (15 kg s ±1 ; Oppenheimer et al 1998) and by direct sampling of high temperature gas (10 kg s ±1 ; Hammouya et al 1998) during a period (February to August 1996) of rapid increase (4±10 m 3 s ±1 ) in dome extrusion rate (Young et al 1998a); however, if the abundant crystallization of plagioclase microlites during magma ascent is taken into account, D Cl has to increase passing from 0.049 wt.% (stage 1; no microlites formed) to 0.084 wt.% (stage 3, with 50% extra microlites; i.e. half of groundmass crystallized; see Fig.…”
Section: Variation Of CL Solubility In Experimental Glassescontrasting
confidence: 70%
See 1 more Smart Citation
“…5). This amount is significantly lower than that observed by open-path infrared measurements (15 kg s ±1 ; Oppenheimer et al 1998) and by direct sampling of high temperature gas (10 kg s ±1 ; Hammouya et al 1998) during a period (February to August 1996) of rapid increase (4±10 m 3 s ±1 ) in dome extrusion rate (Young et al 1998a); however, if the abundant crystallization of plagioclase microlites during magma ascent is taken into account, D Cl has to increase passing from 0.049 wt.% (stage 1; no microlites formed) to 0.084 wt.% (stage 3, with 50% extra microlites; i.e. half of groundmass crystallized; see Fig.…”
Section: Variation Of CL Solubility In Experimental Glassescontrasting
confidence: 70%
“…High Cl emissions from the volcano were also indicated by measurements of HCl fluxes (>15 kg s ±1 or 1300 t day ±1 ) using open-path Fourier transform infrared spectroscopy (OP-FTIR) during July to August 1996 (Oppenheimer et al 1998). Such high Cl emissions are rare for andesitic magma eruptions and arc volcanoes more typically display HCl emissions of 10,000 mol/mol (Symonds et al 1994, and references therein).…”
Section: Introductionmentioning
confidence: 98%
“…Sigvaldason 1974;Shinohara et al 1993;Francis et al 1995). Enhanced volatilisation of HCl from entrained seawater might help to explain these observations, which are further supported by the COSPEC and FTIR measurements of Oppenheimer et al (1998) and Young et al (1998b), which suggested average daily fluxes from Soufrière Hills of 200 tonnes of SO 2 and 3000 tonnes of HCl, the latter approximately twice the value calculated for Mount Etna (Francis et al 1995).…”
Section: Meteorologymentioning
confidence: 54%
“…The raw spectra are analysed for HCl and SO 2 using a forward model. A more detailed description of data reduction procedures may be found elsewhere Oppenheimer et al 1998).…”
Section: Methodsmentioning
confidence: 99%